Species profiles life histories and environmental requirements of coastal fishes and invertebrates--Softshell clam - Newell, Carter R.; Hidu, Herbert (Washington, D.C. U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.53)
Keywords: Invertebrates; Fishes; History; Softshell clam--North Atlantic